Case Report: Adenosine-induced atrioventricular dissociation: unmasking monomorphic tachycardia as a diagnostic challenge in a neonate - Wang, Feifei; Wu, Bin; Huang, Jiaqi; Yaletai, Ba; Liu, Peng (Frontiers in Pediatrics, 2025)
BackgroundNeonatal monomorphic tachycardia poses a diagnostic challenge. This report demonstrates how adenosine-induced AV dissociation confirmed ventricular tachycardia.CaseA 3-day-old preterm neonate (34 + 2 weeks) presented with refractory monomorphic tachycardia (217 bpm; QRS 92 ms) initially diagnosed as SVT based on 1:1 retrograde P-waves. Adenosine administration induced atrioventricular dissociation without termination—a finding inconsistent with SVT. Retrospective ECG analysis revealed prolonged QRS duration during tachycardia (92 ms vs. 60 ms post-cardioversion) and delta wave-like slurring, confirming VT diagnosis. Synchronized cardioversion (0.5 J/kg) restored sinus rhythm, followed by metoprolol prophylaxis.ConclusionThis case highlights that monomorphic tachycardia in neonates may represent VT. Adenosine's role in inducing AV dissociation is pivotal for diagnosis, and low-energy cardioversion with β-blocker maintenance offers an effective rescue strategy. Clinicians must reassess ECG features dynamically to avoid misclassification.